The Use of Technology in English Language Teaching: Benefits and Challenges (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
In the digital age, technology plays a pivotal role in shaping educational practices. This thesis explores the integration of technology in English Language Teaching (ELT), particularly in secondary education. It examines how tools like digital platforms, online resources, multimedia, and mobile applications are revolutionizing language instruction. While technological integration in ELT offers numerous advantages such as increased engagement, personalized learning, and access to authentic materials, it also presents challenges including digital divide, teacher preparedness, and technical limitations. A case study of a vocational school in Uzbekistan further illustrates practical implementation and outcomes. This thesis aims to provide a balanced analysis and offer pedagogical implications for language educators and policymakers seeking to optimize the use of educational technology in English classrooms.